DESIGNING READY-TO-WEAR DELUXE FASHION WITH LONTARA BUGIS MOTIFS USING PLASTIC BAG WASTE AND STITCHING TECHNIQUES - Valerie, Gricel; Tanzil, Marini Yunita; Tahalele, Yoanita Kartika Sari (MODA, 2024)
Plastic bag waste is one of the largest pollutants damaging the environment. Due to its single-use nature, the impact on the environment is severe. Therefore, the reuse of plastic bag waste is essential. Additionally, the use of Bugis Lontara script, a cultural language, is becoming unrecognized by the younger generation when it is a unique identity of a country. Promoting the Bugis Lontara script is hoped to help raise awareness among public. The project will be a ready-to-wear deluxe party attire. The research method used is qualitative. Primary data collection was conducted through interviews with 6 experts and 12 extreme users, while secondary data sources were obtained from scientific journals, reference books, and online articles. The design stages used are the Design Thinking Stages. Based on primary and secondary data, it was found that the production of plastic bag waste continues to rise annually, and various recycling methods are being implemented in the fashion industry. Moreover, the use of the Bugis Lontara script is rarely known or used, with many young people unaware of it. Therefore, preservation actions are necessary through the fashion industry. The application of motifs is done entirely by hand, enhancing the value of the clothing, which is realized in the form of party attire.